2000
DOI: 10.1038/sj.cgt.7700083
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of cancer vaccine therapy using cells transduced with the interleukin-12 gene combined with systemic interleukin-18 administration

Abstract: We introduced the interleukin-12 (IL-12) gene into mouse renal cell carcinoma (RenCa) cells to develop a tumor vaccine and to examine mechanisms of tumor rejection. IL-12-secreting RenCa (RenCa/IL-12) cells were completely rejected when implanted into syngeneic BALB/c but not athymic nude mice, suggesting that T cells were involved in this antitumor effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 29 publications
1
34
0
Order By: Relevance
“…Tumor cells were washed once with PBS and then incubated with 50 g of MMC per 10 7 cells for 1 h at 37°C (14), after which they were washed four times with PBS before use in vivo (as vaccines) or in vitro (to stimulate T cell responses).…”
Section: Methodsmentioning
confidence: 99%
“…Tumor cells were washed once with PBS and then incubated with 50 g of MMC per 10 7 cells for 1 h at 37°C (14), after which they were washed four times with PBS before use in vivo (as vaccines) or in vitro (to stimulate T cell responses).…”
Section: Methodsmentioning
confidence: 99%
“…Single-cell suspensions of spleen cells were prepared by gently pressing spleen cells through a sterile stainless steel 60-gauge mesh screen into cold RPMI 1640 supplemented with 10% heat-inactivated FBS and L-glutamine. RENCA and L1C2 (i.e., syngeneic tumor control) BALB/c tumor cells were used as stimulator cells, and were pretreated with mitomycin C (MMC) using a modification as previously described (36). Briefly, trypsinized RENCA and L1C2 tumor cells were incubated with 50 g/ml MMC at 37°C for 30 min followed by washing to remove MMC.…”
Section: Tumor-specific Lymphocyte Proliferation Assaymentioning
confidence: 99%
“…To perform this study, we isolated mononuclear cells from the spleen of the RENCA tumor-bearing animals that were treated with systemic IL-2 alone, intratumor CXCL9 alone, a combination of systemic IL-2 and CXCL9, or control-treated groups and performed mixing experiments with MMC-pretreated RENCA cells or syngeneic BALB/c L1C2 lung cancer cells pretreated with MMC using a modification as previously described (36). MMC has been shown to be able to completely block the proliferation of RENCA cells and L1C2 cells (36).…”
Section: Combined Systemic Il-2 and Intratumor Cxcl9 Therapy Induced mentioning
confidence: 99%
“…22,23 The therapeutic benefit of RENCA-H6 vaccine seems to be more pronounced when compared with other vaccines or molecular therapies analyzed in preclinical settings in analogical tumor models. 21,24,25 For example, Hara et al 24 showed that vaccination of (five times in 3-day intervals) with irradiated RENCA-wt (control) or RENCA-H6 cells. Fourteen days later viable cells were suspended in Matrigel and implanted s.c. into naive and immunized mice distally from the vaccination site.…”
Section: Discussionmentioning
confidence: 99%
“…21,24,47 Indeed, in mice immunized with RENCA-H6 vaccine subcutaneous RENCA tumors were densely infiltrated by activated CD4 þ and CD8 þ T lymphocytes. In our previous studies in a murine model of malignant melanoma we have shown that vaccination with H6-modified cells induced Th1 and Tc1 immune responses characterized by the presence of antigenspecific, IFNg-secreting CD4 þ and CD8 þ T lymphocytes.…”
Section: Discussionmentioning
confidence: 99%